Life cycle assessment approach of silviculture and timber harvesting of Norway spruce – a case study in the Czech Republic - Hájek, Miroslav; Pulkrab, Karel; Purwestri, Ratna Chrismiari; Tichá, Marie; Paduchová, Martina (Frontiers in Forests and Global Change, 2024)
Compared to other sectors, the long rotation period in forest management makes it difficult to carry out a life cycle assessment (LCA). Data collection is not possible in a short time frame but would require decades. For this reason, forestry is often forced to rely on secondary data. To address this challenge, environmental impacts of the forestry sector in the Czech Republic were investigated according to the value chain corresponding to silvicultural and harvesting processes, without any further wood use options. The methodological procedure is based on the ISO 14040 and 14044 standards, using SimaPro, an LCA software. The study was carried out in four phases of LCA in the scope of cradle-to-gate and focused on the early stages of the product life cycle. The system boundaries were set up to include seed collection, seedling production, establishment and tending of young forest stands up to 20 years of age, thinning, harvesting, maintenance of roads and extraction trails, with the endpoint is the hauling place. Three scenarios have been defined that differ in the method of harvesting. Scenario I– chainsaw felling, horse extraction. Scenario II– chainsaw (90% of hours worked) and harvester (10% of hour-worked), tractor extraction. Scenario III– chainsaw (23 % of hour-worked) and harvester (77 % of hour-worked), extraction by a tractor with a winch. The results show that the maintenance of the forest road network holds a significant share of the overall environmental impact of forest management. Other significant consequences are associated with timber harvesting. These impacts vary considerably depending on the mechanical equipment used. The highest impact was recorded for the third scenario, still, it is practically the most often applied, as it is the most cost-effective. The results show the need to optimize forest management practices in the future both from an economic and environmental point of view. This research was based on long-term knowledge of forest typology, forest management planning, forest economics, experience with forest technologies, and regulatory measures. Thus, the findings serve for further analysis of LCA in timber production, and future analysis for other forest ecosystem services.